Sedierung, tägliche Aufwachversuche und Weaning: Sind die Konzepte der Intensivmedizin auf die Neurointensivmedizin übertragbar? = Sedation and weaning in neurocritical care : Can concepts from general critical care be applied? - Bösel, Julian; Dziewas, Rainer (Der Nervenarzt, 2012)
The translation of modern principles of sedation and weaning from mechanical ventilation from general intensive care to neurocritical care has to take into account specific aspects of brain-injured patients. These include interactions with intracranial hypertension, disturbed autoregulation, a higher frequency of seizures and an increased risk of delirium. The advantages of sedation protocols, scoring tools to steer sedation and analgesia and an individualized choice of drugs with emphasis on analgesia gain more interest and importance in neurocritical care as well, but have not been thoroughly investigated so far. When weaning neurological intensive care unit (ICU) patients from the ventilator and approaching extubation it has to be acknowledged that conventional ICU criteria for weaning and extubation can only have an orienting character and that dysphagia is much more frequent in these patients.
Paralleltitel von Frontdoor übernommen
Gesehen am 15.10.2018